THE EFFECT OF USING DRAMA TECHNIQUE IN TEACHING SPEAKING SKILL TO THE SECOND SEMESTER STUDENTS OF ISLAMIC ECONOMICS AT UNISNU JEPARA IN 2013/2014 - Dwi Erlin Effendi (Tarbawi : Jurnal Pendidikan Islam, 2015)
Speaking is the basic tool of education and the most important skill in everyday life. However, the fact shows that generally many students are inhibited to speak English. Drama can foster language skills such as reading, writing, speaking and listening by creating a suitable context. Drama  is  a  powerful  language  teaching  tool  that  involves  all  of  the students interactively all of the class period. Drama can also provide the means for connecting students??emotions and cognition as it enables students to take risks with language and experience the connection between thought and action. The objective of the study isinvestigating the effect of using drama technique in teaching speaking skill.The study employed a quantitative method, with quasi experimental design with non- equivalent control group. The subjects are the second semester students of Islamic Economics at UNISNU Jeparain academic year 2013/ 2014. The data will be obtained from the result pretest/ posttest. The result in speaking without drama is 65% and the average score is 75,94. Then, the calculation of T-test show that T count is higher than T Table. So, the speaking method by using drama is more effective than without using drama for helping student to improve their ideas of the second semester of Islamic Economy Students of UNISNU Jepara in the academic year of2013/2014.Keywords: speaking ability, dramaBerbicara adalah alat dasar pendidikan dan keterampilan yang paling penting   dalam   kehidupan   sehari-hari.   Namun,   fakta   menunjukkan bahwa pada umumnya  siswa terhambat untuk  berbicara  bahasa  Inggris. Drama dapat memupuk keterampilan bahasa seperti membaca, menulis, berbicara dan mendengarkan dengan menciptakan konteks yang sesuai. Drama adalah alat pengajaran bahasa yang kuat yang melibatkan semua siswa secara interaktif semua periode kelas. Drama juga dapat menyediakan   sarana   untuk   menghubungkan   students'emotions   dan kognisi karena memungkinkan siswa untuk mengambil risiko dengan bahasa dan pengalaman hubungan antara pikiran dan tindakan. Tujuan dari  studi untuk  mengetahui efek  menggunakan  teknik  drama  dalam mengajar   berbicara  studi   skill.metode   yang digunakan adalah metode kuantitatif,  dengan  desain  quasi  eksperimen  dengan  kelompok  kontrol non-setara. Subyeknya adalah mahasiswa semester II Ekonomi Islam di tahun akademik UNISNU Jeparain 2013 / 2014. Data tersebut diperoleh dari hasil pretest / posttest. Hasil dalam berbicara tanpa drama adalah65% dan skor rata-rata adalah 75,94. Kemudian, perhitungan acara T-test yang T hitung lebih tinggi dari T Tabel. Jadi, metode berbicara dengan menggunakan drama lebih efektif daripada tanpa menggunakan drama untuk membantu siswa untuk meningkatkan ide-ide mereka dari semester II  Ekonomi  Islam  Mahasiswa  UNISNU  Jepara  pada  tahun  akademik2013/2014. Kata Kunci : kemampuan berbicara, drama